Early Detection of Urinary Incontinence in The Elderly - Prafitri, Lia Dwi; Nurseptiani, Dzikra; Faiza, Hani Irfana (Prosiding University Research Colloquium, 2023)
The increase in age that occurs in the elderly causes the bladder muscles and urinary tract (urethra) to weaken. Incontinence is also often part of the syndrome that occurs in the elderly. Although it is not usually a dangerous condition, urinary incontinence can adversely affect the sufferer’s condition and social life. The purpose of this community service is as an effort to early detect urinary incontinence in the elderly. This activity was carried out on 48 elderly people in Rengas Kedungwuni Village, Pekalongan Regency. The method carried out for urinary incontinence examination uses the SSI (Sandvix Severity Index) scale diagnostic questionnaire, in addition to that blood pressure and weight checks are also carried out and provide education about kegel gymnastics. The results obtained from the examination carried out were that there were 12 elderly people (25%) who experienced urinary incontinence, an average blood pressure of 142 / 77 mmHg, and an average body weight of 55 kg. Early detection efforts obtained data that 25% of the elderly experience urinary incontinence and already know how to overcome it with kegel gymnastics, so follow-up is needed from health workers in conducting early detection of urinary incontinence to reduce morbidity and improve the quality of life in the elderly.